Вы находитесь на странице: 1из 4

.


.
.
.
.
.
.

I.

. ,
,
( : ,
,
.. ,
). ,
, (
).
.
. , ,
.
:
1. :
(a) f (x) = x
(b) f (x) =

P (x)
,
Q(x)

P(x) Q(x)

2. ( ,
, ):
(a)
(b)
(c)
(d)

f (x) = x
f (x) = loga x
( sin x cos x)

,
, , .. .
.
. : ,
:
f (x) = sin (sin (. . . sin (sin x)))

(1)

sin (f (x)) = f (x) = f (x) 0,

(2)

, :

f (x) , . f (x)
, .
1

II.

f : E 7 R E
( - ).
, a E . lim f (x) = f (a),
xa
.
, :
.
:
a x R, a + x E
( , x > 0).
a x
fa (x) = f (a + x) f (a). , ,
(, ) f (a).
.
f (x)
a, lim fa (x) = 0.
x0

Th

. .
, .
:
lim f (x) = f (a) > 0 () > 0 : x |x a| < |f (x) f (a)| <

xa

lim fa (x) = 0 > 0 () > 0 : x |x| <

x0

V |fa (x)| = |f (a + x) f (a)| < (3)


, x = a + x,
.
,
. , :
, , ,
( : , ,
, x0 : x 0
x x0 ).

III.

, , ,

. ,
, . ,
-
. , , .
,
:
1. :
lim f (a + x) f (a) = lim c c = 0

x0

x0

(4)

2. f (x) = x :
lim f (a + x) f (a) = lim a + x a = lim x = 0

x0

x0

x0

(5)

3. (, ) f (x) = P (x):
, x,
. , , , .
4. f (x) =

P (x)
:
Q(x)

. .3

5. f (x) = x :

lim f (a + x) f (a) = lim a+x a = lim a x 1 =

x0

x0
x

= lim a
x0

x0

1
x = lim a ln x = lim C x = 0 (6)
x0
x0
x

6. f (x) = logb x:
a + x
lim f (a + x) f (a) = lim logb (a + x) logb a = lim logb
=
x0
x0
x0
a



logb 1 + x
x
x
1 x
a
= lim logb 1 +
= lim

= lim

= 0 (7)
x
x0
x0
x0 ln b
a
a
a
a
7. f (x) = x : , x = eln(x) ,
( ), , .
8. f (x) = sin x:


x
x
cos a +
=
lim f (a + x) f (a) = lim sin (a + x) sin a = lim 2 sin
x0
x0
x0
2
2
sin x
x
x
= lim 2 x 2
cos a = lim 2
cos a = 0 (8)
x0
x0
2
2
2

. , , , ! , x = 2 + n,
.
, .
.
:
Th
.
f (x) : A B ( A B ),
A f 1 (x) : B A. f 1 (x) B.
I
, x f (f 1 (x)) = x. x a : lim f (f 1 (x)) = lim x = a. .. f (x)
xa 
xa

1
1
, lim f (f (x)) = f lim f (x) = a.
xa

xa

: lim f 1 (x) = f 1 (a), .


xa

a , .
.
: (, sin x : [ 2 ; 2 ] [1; 1]), :
.
.
. , arcsin x
.
.


Оценить